2020
DOI: 10.3390/met10081088
|View full text |Cite
|
Sign up to set email alerts
|

On the Intergranular Corrosion Properties of Thin Ferritic Stainless Steel Sheets Welded by Fiber-Laser

Abstract: In the present investigation, thin sheets of stabilized and unstabilized ferritic stainless steel were welded in butt joint configuration using irradiation of a 1070 nm fiber-laser. Using optical microscopy, the microstructural evolution upon alternating heat input was characterized. In addition to that, hardness and tensile tests were carried out on the specimens. Detailed focus was given to the intergranular corrosion properties, which were investigated on basis of the Strauss test with different times of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…After welding, the values of uniform tensibility and tensibility decreased. In the case of the study performed by Sommer et al [37], the differences in tensibility were not as significant as in our case. It should be noted that in our research, the samples of AISI 430 material were not thermomechanically processed before or after welding.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…After welding, the values of uniform tensibility and tensibility decreased. In the case of the study performed by Sommer et al [37], the differences in tensibility were not as significant as in our case. It should be noted that in our research, the samples of AISI 430 material were not thermomechanically processed before or after welding.…”
Section: Resultscontrasting
confidence: 74%
“…The comparison of the mechanical properties given in Table 4 shows that the laser-welded samples of AISI 430 LW produced higher values of yield strength, lower values of tensile strength, uniform tensibility and tensibility, and no significant changes in the normal anisotropy ratio and strain-hardening exponent compared to the values found in the base samples of AISI 430 BM. Sommer et al [37] observed a similar trend for AISI 430. After welding, the values of uniform tensibility and tensibility decreased.…”
Section: Resultsmentioning
confidence: 62%
“…Moreover, titanium carbides (TiC) or nitrides (TiN) act as inclusions within the surrounding matrix and therefore, again, promote selective corrosion phenomena [14,15]. Along with these observations, intergranular corrosion can also be identified in unstabilized and Ti-stabilized FSS when welded with a fiber-laser under the utilization of very low energy inputs [31]. Based on transmission electron microscopy studies on the precipitation behavior, chromium depletion is the governing factor for intergranular corrosion propagation within welds of unstabilized FSS [32].…”
Section: Introductionmentioning
confidence: 91%
“…Table 1. (a) Chemical composition of AISI 430 and AISI 430Ti sheet material used in the investigation, adopted from [31]. Copyright 2020 Niklas Sommer; (b) Chemical composition of AISI 316L austenitic stainless steel powder, partially adopted from [37] Nominal distribution 20-53 µm, partially adopted with permission from ref.…”
Section: Sheet and Powder Materialsmentioning
confidence: 99%
“…The sheets were laser-cladded in cold-rolled and blank-annealed surface condition. For additional information about the used substrates and clamping devices, the reader may be referred to [25]. AISI 316L austenitic stainless steel with nominal powder size distributions of 20-53 µm (GTV Verschleißschutz GmbH, Luckenbach, Germany), as well as 50-150 µm (DEW Specialty Steel GmbH and Co. KG, Krefeld, Germany) were employed as feedstock.…”
Section: Materials and Process Setupmentioning
confidence: 99%